The role of small industry in the process of economic growth - Shinohara, Miyohei; Fisher, Douglas; Hoselitz, Bert F. (The Hague ; Paris : Mouton, 1968)
This volume is an account of literature on small-scale industry in present day Japan and India.
A series edited by the International Committee for Social Sciences Documentation- vol. III.
Summaries in French.
Includes bibliographical references and index.
osa 09/04/2018
Loans
Keywords: Small business